(untitled) (Journal of Ideas in Health, 2025)
Background: Bartonella are facultative Intracellular gram-negative bacteria from the Bartonellaceae family. Several rodents associated with Bartonella species have been known to be transmitted by ectoparasites to animals and humans however, limited information is available about their epidemiology, host, vector, and species specificity, particularly in southern Tanzania. This study aimed to investigate the prevalence and molecular characterization of Bartonella species in rodents and their associated ectoparasites in Kilwa district, Southern part of Tanzania. Methods: A cross-sectional study was conducted to capture rodents using Sherman and Wire cage traps. Captured rodents were anesthetized using diethyl ether and dissected to extract spleen tissue. Ectoparasites were identified by examining their morphological features with a stereo microscope aided by ectoparasites identification keys. A total of 138 rodent spleen tissue and 93 pools of ectoparasites were subjected to conventional polymerase chain reaction (PCR) and sequencing targeting the gltA gene of Bartonella species. Results: The overall prevalence of Bartonella species in rodents was 3.62% with a statistically significant difference in prevalence among species (χ² = 12.951, df = 5, p < 0.01) compared to 3.23% in ectoparasites with no significant differences across species (p > 0.05). Bartonella infections were 3.37% in M. natalensis, 3.27% in R. rattus and 50.0% in G. dolichurus. The Laelaps species and Xenopsylla cheopis were found infected by 6.67% and 2.70%, respectively, while Rhipicephalus appendiculatus was not infected by Bartonella species. Sequence analysis of rodents and ectoparasites showed that the obtained sequences in the current study were genetically closely related to Bartonella mastoids from Turkey, Bartonella species from Kenya, and uncultured Bartonella species from South Africa (99.50–99.75% identity). Conclusion: The detection of Bartonella species in rodents and their associated ectoparasites implies the reservoir role of rodents and vectors in transmitting Bartonella species to humans and animals. The results suggest that further epidemiological studies need to be done to determine whether the identified Bartonella species could be responsible for animal and human cases of febrile illness in an area.